PENGEMBANGAN PEMIKIRAN PENDIDIKAN ISLAM DENGAN PENDEKATAN TAFSIR TEMATIK - BUKHARI UMAR (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2011)
Education is human’s problem. Human is a dynamic creature. The dynamics of human’s life demands dynamic educational process in order to fulfill human’s needs. In order to maintain the dynamic thoughts of Islamic education, some relevant studies are needed. Revelation based Islamic education studies can develop the concept of Islamic education and avoid the possible mistakes made by researchers in education fields. In doing so, the researchers may use tafsir thematic approach. This is made possible since al-Quran contains much information concerning with education and guides and leads any activities of man’s thoughts into those which are suitable of Islamic teaching as well.Kata kunci: pengembangan pemikiran, pendidikan islam, tafsir tematik